MAKNA PEREMPUAN ADALAM AKUN INSTAGRAM @PENDAKICANTIK BAGI PENDAKI PEREMPUAN DIKALANGAN KOMUNITAS PENGGIAT RIAU - Ismsrwan "; Genny Gustina Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Climbing the mountain is an heavy activity and generally doing by men. But also was interested by women right now. This activity not only doing by men but also women. Nowadays women mountaineer could seeing from the media aplication is instagram account @pendakicantik. The purpose of this research is to find out the motives. The meaning of women mountaineer who showing by instagram account @pendakicantik.He method of this research is with kualitatif reasearch. Informan of this research consist of five women which is came from Komunitas Penggiat Riau who was choosing by purposive sampling. The technique of data's collection is by deeply interview, observation and documentation.Result of the research Komunitas Penggiat Riau show the motive consist of because love the beauty of nature, as an entertainment, love the challenge, and as adding the experience. The other motive is in order to motive, that purpose is to dispense hobby and looking for other friends. The meaning of women mountaineer by Komunitas Penggiat Riau is strong women and independent. The meaning women mountaineer by instagram account @pendakicantik is the pretty women and motivate the other women to do that activity.